From mindfulness to work engagement: The mediating roles of work meaningfulness, emotion regulation, and job competence - Chen, Liang; Li, Xiaobei; Xing, Lu (Frontiers in Psychology, 2022)
Drawing from the grounded theory of work engagement, this research aims to explore three essential yet previously unexamined pathways—work meaningfulness, emotion regulation, and job competence in simultaneously transmitting the effects of mindfulness training to employee experience of work engagement. We employed a six-wave quasi-experimental design and recruited 129 employees (77 from experimental group and 59 from control group) to participate in the quasi-experiment, and tested our simultaneous mediating models using the structural equation modeling. Results showed that mindfulness facilitated employees’ work meaningfulness, emotion regulation, and job competence, which in turn enhanced employee work engagement. By doing so, we add to the mindfulness literature by showing that the three essential psychological states are important machanims that link mindfulness to work engagement. Practicially, this research reveals that mindfulness training is an effective tool to influence employees’ psychological states (e.g. meaningfulness, competence), which ultimately develop their work engagement in the workplace.